Hallux varus: A literature review. (December 2021) - Mohan, Rahul; Dhotare, Satish V.; Morgan, Samer S.
Highlights: Hallux varus is a rare foot deformity caused by iatrogenic, post-traumatic, idiopathic, inflammatory, spontaneous and congenital pathologies. Among these iatrogenic is the most common. Hallux varus is caused by abnormal musculotendinous forces secondary to soft tissue or bony imbalance exerting a varus deforming force. Understanding the anatomy of the hallux stabilisers and the pathophysiology of hallux varus is vital in its management. It is also essential to understand the potential surgical pitfalls leading to iatrogenic hallux varus to avoid its occurrence. Abstract: Hallux varus is a rare foot deformity due to iatrogenic, post-traumatic, idiopathic, inflammatory, spontaneous, or congenital pathologies. Acquired hallux varus, in particular, iatrogenic type, is the commonest. The primary pathology is the abnormal musculotendinous forces secondary to soft tissue or bony imbalance exerting varus deforming force. Understanding the anatomy of the hallux stabilisers and the pathophysiology of hallux varus is vital in its management. It would be helpful to understand the potential surgical pitfalls leading to iatrogenic hallux varus. This literature review summarises all the published facts about hallux varus, focussing on anatomy, pathophysiology, clinical and radiological assessment, and management.